Rhetoric and courtliness in early modern literature - Richards, Jennifer (Cambridge University Press, 2003)
This book explores the early modern interest in conversation. Conversation was widely accepted to have been inspired by the philosopher Cicero. Recognising his influence on courtesy literature - the main source for 'civil conversation' - Jennifer Richards uncovers new ways of thinking about humanism as a project of linguistic and social reform.